(untitled) (Nepal Medical College Journal, 2024)
Staphylococcus aureus is a frequent cause of bacterial infections ranging from minor skin infections to fatal necrotizing infections and infections are on the rise particularly the hospital-acquired infections. The infections becomes more complicated when the infection are caused by drug (methicillin) resisant S. aureus. Therefore, detection of methicillin-resistant S. aureus (MRSA) becomes important. In this study, thus, we investigated the mecA gene in 53 S. aureus isolates isolated from health care workers (n= 213). Of the total 53 S. aureus isolates tested in this study, 24 (45.3%) were positive for mecA gene (533bp). Present study showed a relatively higher rate mecA gene positivity.